Timing and intensity of physical activity and late sleeping habits among children in Japan - Matsuyama, Yusuke; Isumi, Aya; Doi, Satomi; Shibata, Ai; Ishii, Kaori; Oka, Koichiro; Fujiwara, Takeo (Frontiers in Pediatrics, 2022)
Background: Little is known about what timing and intensity of physical activity is beneficial to prevent children’s late sleeping habit. We investigated the association between timing and intensity of physical activity and late sleeping habit among Japanese children. Methods: The amount of physical activity in a weekday (light (>1.5 to <3.0 METs); moderate (3.0 to <6.0 METs); and vigorous (6.0 to <20.0 METs)) was measured for the whole day, before school, during school, and after school, using accelerometers for population-based fourth-grade elementary school and eighth graders for seven consecutive days between September and December 2018. Late sleeping habit (going to bed after 10 p.m. for fourth graders and after 11 p.m. for eighth graders) was assessed by questionnaires. The data of 229 fourth graders and 182 eighth graders were analyzed with Poisson regression adjusted for grade, gender, household income, body-mass index, belonging to sports club, wake-up time on weekdays, and physical activities with different intensity. Results: Total physical activity was not associated with late sleeping habit. Light-intensity physical activity before school was protectively associated with late sleeping habit (prevalence ratio: 0.82, 95% confidence interval: 0.68, 0.99), while physical activity at school or after school was not. Conclusion: Light-intensity physical activity before school may enhance earlier bedtime of children.